Lithofacies Analysis and Reconstruction of Deformation Types of Cenozoic Sediments of Phú Khánh Basin - Trần, Nghi (VNU, 2014)
From Oligocene and Quaternary geological sedimentary section have six cycles corresponding to six sequences: - Sequence 1: Eocene - early Oligocene (E2 – E 3 1 ); - Sequence 2: Late Oligocene (E3 2 ); - Sequence 3: Early Miocene (N1 1 ); - Sequence 4: Middle Miocene (N1 2 ); - Sequence 5: Late Miocene (N1 3 ); - Sequence 6: Pliocene - Quaternary (N2 - Q). Since then may establish three general integrated formulas between the lithofacies association series and sedimentary systems tract as follows: 1. Sedimentary lowstand systems tract (LST): LST = arLST + (ar + amr)LST + (amt + mt)/(amr + mr) LST + mrLST (1); 2. Sedimentary transgressive systems tract (TST): TST = MtTST + atTST + (amr + mr)/(mt + amt)TST + mtTST (2); 3. Sedimentary highstand systems tract (HST): HST = arHST + (ar + amr)HST + (amt+mt)/ (amr +mr)HST + mrHST (3).